Kinerja Ditinjau dari Gaya Kepemimpinan, Lingkungan Kerja dan Beban Kerja: Studi Kasus pada Satlantas Polres Kabupaten Wonogiri - JuwitaSari, Helmaliana; Sri Hartono; Istiqomah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was conducted to determine the influence of leadership style, work environment and workload on the performance of the Wonogiri Regency Police Traffic Unit. This type of research uses quantitative descriptive research. The sampling technique was carried out using a saturated sampling technique (census) with a total of 83 respondents taken from all members of the Wonogiri Regency Police Traffic Unit. The data analysis technique uses multiple linear regression tests. The test results show that the leadership style with tcount 2.567 > ttable 1.990 has a significant effect on the performance of the Wonogiri Police Traffic Unit. The test results show that a work environment with tcount 2.888 > ttable 1.990 has a significant effect on the performance of the Wonogiri Police Traffic Unit. The test results show that the workload with tcount 2.820 > ttable 1.990 has a significant effect on the performance of the Wonogiri Police Traffic Unit. The results of the research state that leadership style, work environment and workload have a positive and significant influence on the performance of the Wonogiri District Police Traffic Unit.